EUFORIA MERGER – HARGA SAHAM DAN TRADING VOLUME BRIS - Taufiq Andre Setiyono; Rinwanti Rinwanti (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to obtain empirical evidence regarding the differences in the stock price of BRIS before and after the merger of the three sharia banks of BUMN, and to obtain empirical evidence regarding the difference in trading volume of BRIS stock before and after the merger of the three sharia banks of BUMN. In this research, the analytical method used paired sample t-test with the SPSS program. The object of this research is BRIS. This study concludes that there is no difference between the stock price of BRIS before and after the merger of of the three sharia banks of BUMN, and there is a significant difference between the trading volume of BRIS stock before and after the merger of the three sharia banks of BUMN.